Synthesis and Characterization of New Copper(II) Substituted Dicalcium Phosphate Dihydrate (CaHPO4·2H2O) - El Hamidi, A.; Halim, M.; Arsalane, S.; Kacimi, M.; Ziyad, M. (Asian Journal of Chemistry, 2012)
We have investigated, in aqueous solution, the exchange process of calcium by copper (Ca2+/Cu2+) and its effects on the chemical and structural stability of dicalcium phosphate dihydrate (CaHPO4·2H2O). The compounds obtained at different concentrations of Cu2+ and various pH were characterized by X-ray diffraction, spectroscopically, chemical analysis and SEM-EDS microscopy. The combined results of these methods, confirmed that copper ions incorporate partially the dicalcium phosphate dihydrate framework by the exchange of Ca2+ ions with copper favouring the formation of Ca1-xCuxHPO4·2H2O solid solution which is isomorphic to the pure dicalcium phosphate dihydrate. The upper limit of copper solubility in dicalcium phosphate dihydrate is observed at 25 %. Unlike calcium, Cu2+ ions prefer to be hosted by low symmetry sites in dicalcium phosphate dihydrate structure causing a slight compression of the unit cell. This exchange inhibits the nucleation of derived hydroxyapatite compounds frequently observed with many other divalent cations. The dehydration in air at 250 ºC of dicalcium phosphate dihydrate - % Cu2+ can lead to the formation of stable anhydrous products Ca1-xCuxHPO4 (DCPA) with monetite structure.